Profil Pemimpin Publik: Studi Deskriptif mengenai Kepemimpinan pada Generasi Milenial - Anissa Lestari Kadiyono; Gianti Gunawan (Psympathic : Jurnal Ilmiah Psikologi, 2020)
The objective of this research is to describe the type of Indonesian leader expected by millennials based on the exploration of task, relationship, and change orientation. Millennials are currently reaching 30% of the Indonesian population. Their voices can determine what kind of leaders that are expected to lead Indonesia. This research is a quantitative method with a survey technique. The sampling method conducted using convenience sampling and there are 275 respondents who are millennial beginner voters, consisting of students from 26 universities spread across Indonesia. The results show that the value that should be in the leader according to millennials is leaders who showed the real work, responsible, and decisive person. The change orientation shows a higher domination compared to the orientation of the task orientation and relationship orientation.